Hubungan Penurunan Fungsi Gerak Lansia terhadap Strategi Koping Stres Lansia di Panti Jompo Welas Asih Kec. Singaparna Kab. Tasikmalaya - Permana, Fanji Helvi; Sumarwati, Made; Rosyadi, Imron (Jurnal Keperawatan Soedirman, 2009)
Activity function decline become one of the stress causes for elderly that can disturb Activity Daily Living (ADL). The Stress condition makes elderly to adapted that alteration by using coping strategy, they are Problem Focused Coping (PFC) and Emotional Focused Coping (EFC). The aim of this research is to know the correlation between activity function decline to stress coping strategy in elderly.This research used analytic correlation with cross sectional approach design. Purposive sampling technique was applied to determine sample. Chi-Square statistical analysis was used to analyze the data. The samples who had a part decline were 25 people (83,3%) and the samples who had a total decline were 5 people (16,7%). The quantity samples who used PFC coping strategy was 24 people (80%) and EFC was 6 people (20%). Based on the Chi square analysis, p value was 0,298. Because p value was more than ? (5%) or 0,05, it meant that there were not correlation significantly between activity function decline to stress coping strategy.There was no correlation between activity function declines to stress coping strategy of elderly in nursing home â€œWelas Asihâ€, Singaparna, Tasikmalaya.